“Risk Score for Development of Veno-Occlusive Disease After Allogeneic Hematopoietic Cell Transplant” - Strouse, Christopher (Biol Blood Marrow Transplant, 2018)
BACKGROUND: A risk score identifying patients at high risk for veno-occlusive disease (VOD) may aid efforts to study preventive strategies for this uncommon complication of hematopoietic cell transplantation (HCT). METHODS: Patients receiving a first allogeneic HCT between 2008–2013 as reported to the Center for International Blood & Marrow Transplant Research (N=13,097) were randomly divided into training and validation sets. Independent prognostic factors for development of VOD by day+100 post HCT were identified with a multivariate logistic regression model. A risk score was constructed in the training set using the significant factors and confirmed in the validation set. RESULTS: Baseline characteristics of the training and validation sets were balanced. In total, 637 patients (4.9%) developed VOD by day+100. Younger age, positive hepatitis B/C serology (HBV, HCV), lower Karnofsky performance score (KPS), use of sirolimus, disease, disease status at transplant, and conditioning regimen were independent prognostic factors. Myeloablative (MAC) regimens were associated with higher risk of VOD. Busulfan-based MAC regimens guided by pharmacokinetic monitoring (PK) were associated with higher risk than those without PK. The patients were stratified into 4 distinct, statistically significantly different groups by their risk score percentile. CONCLUSION: This pre-transplant risk score successfully stratified allogeneic HCT patients by risk of developing VOD, was validated in an independent set, and demonstrated strong discriminatory ability to identify a high-risk cohort.